ANALISIS PENGARUH VARIASI FAKTOR PRIORITAS PENGGUNAAN PRASARANA PERKERETAAPIAN TERHADAP TRACK ACCESS CHARGES (TAC) - , Sekar Mayang ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Railway is one of the available transportation modes in Indonesia, in Java and Sumatera which is used for carrying the passengers and freights. People choose to use railway because it is a fast transportation mode and has its own track which aside from traffic jam. In Precidential Regulation Republic of Indonesia Numb. 53 in 2012, it is explained that every railways operator which use railways infrastructure have to pay Track Access Charges (TAC) to Government. The rules of the calculation of TAC which have to be paid by PT.KAI are explained in Regulation of Transport Minister Numb. 62 in 2013 about The Rule of Calculation Rail Infrastructure Charges State Owned. In Regulation of Transport Minister Numb. 62 in 2013, there is priority factor which has same value for every service type of the train (Fp=1). Actually, every service type of railway has different priority and give different damages for infrastructure based on the speed. This research intended for analyzing the influence of priority factor to TAC. Quantitative description method is a method which is used in this research. The objects of the research are Executive, Bussines, and Economic class of passenger train in Java. The calculation of TAC based on Regulation of Transport Minister Numb. 62 in 2013 with the variations in priority factor (Fp). It suggested with two ways calculation which oriented on railway travel time. Then, the best Fp is chosen which represented the real condition where the train with higher priority has to paid TAC more expensive the the others. The result of this research, with Fp=1 average TAC for Economic class is 68.00 Rp/GT/km, for Executive class is 30.00 Rp/GT/km, while for Bussines class is 28.00 Rp/GT/km. There are two ways to calculate Fp. The first way generates Fp= 1.39 for Executive class and gives 42.00 Rp/GT/km for the average TAC, while Fp=1.21 for Bussines class and generates 34.00 Rp/GT/km for average TAC. The second way generates Fp=3.00 for Executive class and it gives 91.00 Rp/GT/km while for Bussines class it generates Fp=2.00 and it gives 56.00 Rp/GT/km. the calculation of TAC with second way is more represents the real condition, where Executive class has higher priority and speed then the other classes, so it has to pay higher TAC too.